background image

A.1. LOGIC OF GENERALIZATION

389

a, b

R

.

M

(

a

) =

E

1

a

;

M

(

b

) =

E

1

b

;

E

1

a

=

E

1

b

; thus

a

=

b

because

E

1

is

a bijection.

a

R

,

b /

R

.

M

(

a

) =

E

1

a

;

M

(

b

) = (

t, b

);

M

(

a

)

S

;

M

(

b

)

/

S

. Thus

M

(

a

)

6

=

M

(

b

).

a /

R

,

b

R

. Analogous.

a, b /

R

.

M

(

a

) = (

t, a

);

M

(

b

) = (

t, b

). Thus

M

(

a

) =

M

(

b

) implies

a

=

b

.

Theorem

1955

.

M

E

= id

S

.

Proof.

Let

x

S

. Then

Ex

R

;

M

(

Ex

) =

E

1

Ex

=

x

.

Obvious

1956

.

E

=

M

1

|

S

.

A.1.2. Existence of primary filtrator.

Theorem

1957

.

For every poset

Z

there exists a poset

A

Z

such that (

A

,

Z

)

is a primary filtrator.

Proof.

Take

S

=

Z

,

B

=

F

,

E

=

. By the above there exists an injection

M

defined on

F

such that

M

◦ ↑

= id

Z

.

Take

A

= im

M

. Order (

v

0

) elements of

A

in such a way that

M

:

F

(

Z

)

A

become order isomorphism. If

x

Z

then

x

= id

Z

x

=

M

x

im

M

=

A

. Thus

A

Z

.

If

x

v

y

for elements

x

,

y

of

Z

, then

x

v↑

y

and thus

M

x

v

0

M

y

that is

x

v

0

y

, so

Z

is a subposet of

A

, that is (

A

,

Z

) is a filtrator.

It remains to prove that

M

is an isomorphism between filtrators (

F

(

Z

)

,

P

) and

(

A

,

Z

). That

M

is an order isomorphism from

F

(

Z

) to

A

is already known. It

remains to prove that

M

maps

P

to

Z

. We will instead prove that

M

1

maps

Z

to

P

. Really,

x

=

M

1

x

for every

x

Z

.